Study on the Influence of Processing Parameters on Piercing Extrusion Process of Large Diameter Cupronickel Alloy Pipes Using 3D FEM Analysis - Jun Cai; Kuaishe Wang; Bing Zhang; Wen Wang (Advances in Materials Science and Engineering)
With the rapid development of the shipping and the power industry, the demand for high-performance cupronickel alloy pipes is greatly increasing. The main processing methods of this alloy include semisolid ingot casting and deformation by hot extrusion. Many defects appear during the hot extrusion process for large diameter cupronickel alloy pipes, which results in considerable problems. Therefore, numerical simulation of hot extrusion for cupronickel alloy pipes before the practical production is of vital significance to properly determine the deformation parameters. In order to obtain the influence of processing parameters on the piercing extrusion process of large diameter cupronickel alloy pipe, metal flowing law under different deformation conditions was simulated and analyzed via employing a 3D FEM code. The results showed that piercing speed had no obvious influence on the cupronickel alloy billet. However, the friction had significant influence on the piercing process of cupronickel alloy billet: with the increase of friction coefficient, the temperature and the load increased.